Conflict Matters. Peace and Conflict Education Practices Towards SDG16 - Cécile Barbeito (Universidad Autónoma de Madrid, 2019)
SDG16 aims at fostering peaceful and inclusive societies and accountable and inclusive institutions. (How) can this be achieved through peace education? The article evaluates the extent in which 25 European peace education practices succeed contributing to the accomplishment of sdg16 regarding the decrease of violence and the improvement of democratic institutions. Taking into account peacebuilding literature that highlights the importance of institutionalizing peace education initiatives, the article analyses the objectives, target, approaches, results and impacts of the 25 initiatives, and assesses to what extent they address the micro, meso, and macro level. Results show that a relatively high proportion of objectives (23,9%) focus on the institutional-school level, that most of them target multipliers (as teachers and school staff) and that many practices prioritise a preventive approach. Regarding results and impacts, outstanding results are reached in skills development for conflict transformation, but that this does not imply significant reductions of violent situations. While most of the practices aim at more comprehensive results than violence contention -but rather a broader conception of peaceful coexistence- very few take action to foster the participation of students in the school system. Further research is needed to identify indicators of structural and cultural violence at schools, to assess the effectiveness of mainstreaming peace and conflict education principles in the school institution to decrease violence, and about the educational policies that better contribute to effective peace and conflict education programs.